Patterns of Communicative Interaction in the Mathematics Classroom - Leguizamón Romero, José Francisco; Universidad Pedagógica y Tecnológica de Colombia (UPTC Editorial, 2023)
This book analyses aspects of profesional practice, especially the patterns of communicative interaction of professors of the Bachelor of Mathematics at UPTC and their resignification based on reflection on their own practice. For this purpose, four main topics were used as reference points: interactions; the professors’ pedagogical and didactic models; the didactic analysis of a class, emphasizing the onto-semiotic approach to mathematical cognition, which was taken as a reference for this study; and communication, understood as a social interaction mediated by language, in which the objective of each subject is to understand and be understood. This research corresponds to a mixed study with qualitative predominance, interpretive descriptive approach and case study methodology. The fieldwork consisted of activities carried out within the Collaborative Work Group, composed of three professors and the researcher, all with a Degree in Mathematics from the UPTC, in which they reflecte on the pedagogical practice of the participants in the group. A complete analysis was carried out before, during and after the collaboration, which made it posible to identify aspects of resignification. One of the fundamental conclusions of the research is that, at the end of the work with the collaborative workgroup, the professors were able to give a new meaning to their profesional practices, moving from a class typology with unidirectional characteristics to one with reflective characteristics. They also managed to resignify the patterns of communicative interaction, since in the first phase patterns were presented that centered on the professor, but later they focused on the student.